The Efforts to Improve the Speaking Skills of Elementary School Students Using the Story-Telling Learning Method in Bekasi City: Upaya Meningkatkan Keterampilan Berbicara Siswa Sekolah Dasar Menggunakan Metode Pembelajaran Story Telling Di Kota Bekasi - Anisa, Ririn (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2023)
This study aims to improve the speaking skills of fifth-grade students at SDS Galajuara Bekasi using the story-telling method. The research was carried out using the Classroom Action Research (CAR) method using the DDAER design (diagnosis, design, action and observation, evaluation, reflection) which was carried out in 2 cycles with 28 students in class V as research subjects. The results showed an increase in students' speaking skills. In the first cycle, completeness was obtained by 78.6%, or as many as 22 students, and 21.4%, or as many as 6 students still not complete. Meanwhile, in the implementation of the second cycle, the students' completeness data was obtained by 89.3%, or as many as 25 students completed and 10.7%, or as many as 3 students were still in the incomplete category. The final result of the average value of students' speaking skills obtained in the second cycle is 80.4.